Energy Harvesting (IntechOpen, 2023)
This book contains chapters that discuss numerous methods and techniques in energy harvesting. Both theoretical and experimental results are presented from investigations that were carried out in the various chapters. Well-grounding methods and techniques presented in the new areas provide a good head start not only to those with interest in energy harvesting but also to experienced researchers who may want to look at energy harvesting from different angles. The concepts of energy harvesting are well articulated in the introduction of each chapter. It is my sincere hope that the readers of this book will find it a useful fountain of knowledge in energy harvesting.